Penetapan Batas Maksimal Bunga Pinjaman Pemegang Saham kepada Entitas Anak Perusahaan berbentuk Emiten atau Perusahaan Publik - Novansyah Siregar; Herdiasti Anggitya Dwisani; Alfit Jenifer (Syntax Corporation Indonesia, 2024)
In today's business activities, many companies in Indonesia choose to obtain funds from shareholders through loans from shareholders, compared to the mechanism of increasing issued and paid-up capital. Specific to subsidiaries with the status of public companies or issuers, the scheme of obtaining funds from shareholders through shareholder loans is considered relatively easier because it is an affiliate transaction. This study will further examine the appropriate form of regulation related to the determination of the maximum limit of shareholder loan interest to subsidiary entities in the form of issuers or public companies. Through a normative juridical approach with qualitative analysis methods, this study explores the existing regulatory framework, identifies gaps in implementation, and formulates comprehensive regulatory solutions. The results of the study revealed several important findings. First, the existing regulatory framework does not provide clear parameters regarding the maximum limit of interest on shareholder loans, causing inconsistencies in business practices. Second, the existing supervision and enforcement mechanisms have not been optimal in preventing potential abuse of shareholder loan schemes. Third, an integrative approach is needed that considers the legal aspects of the company, the capital market, and taxation in determining the maximum reasonable interest limit. This study recommends the establishment of a special regulatory framework that regulates the determination of the maximum limit of shareholder loan interest.